The Influence of Artificial Intelligence Usage Intensity on Information-Seeking Habits among Generation Z - Ana Vivtia Setyawan; Mimi Wahyuni (Asosiasi Dosen Muda Indonesia, 2026)
The rapid advancement of generative artificial intelligence (AI) has significantly transformed how individuals access, process, and utilize information, particularly among Generation Z. This study aims to examine the influence of artificial intelligence usage intensity on the information-seeking habits of Generation Z. A quantitative explanatory approach with a cross-sectional survey design was employed. Data were collected through an online questionnaire from 400 valid Generation Z respondents in Indonesia who had experience using AI applications such as ChatGPT, Gemini, Microsoft Copilot, and Perplexity. The collected data were analyzed using descriptive statistics, validity and reliability testing, classical assumption testing, and simple linear regression analysis with IBM SPSS Statistics. The results indicate that artificial intelligence usage intensity has a positive and statistically significant effect on information-seeking habits (β = 0.541, t = 14.744, p < 0.001). The regression model explains 35.3% of the variance in information-seeking habits (R² = 0.353). Respondents demonstrated high levels of AI usage, particularly in search initiation and conversational query formulation, whereas information verification and source comparison obtained relatively lower scores. These findings suggest that AI enhances the efficiency and accessibility of information seeking but does not automatically strengthen critical evaluation and verification practices. The study contributes empirical evidence regarding AI-mediated information behavior among Generation Z and highlights the importance of integrating AI literacy with information literacy to promote responsible, critical, and ethical use of generative AI.